Pengaruh Media Sosial Instagram Dalam Mengiklankan Makanan Cepat Saji dan Dampak Bagi Kesehatan Pada Remaja - Siti Rara Oyi Pinasti (Universitas Majalengka, 2021)
Adolescent nutritional needs need to be considered because in adolescence there is rapid growth and development. Unhealthy eating habits affect adolescent nutritional intake, such as fast food consumed by teenagers. At a time when everything is modern, teenagers want everything to be fast, including in choosing food, namely fast food known to the public as junk food. Junk food is defined as junk food or food that does not have nutrients for the body. Junk food is not only wasteful, it can also be detrimental to health. Fast food comes from western countries which have high fat and calorie content. Many factors influence adolescents to eat fast food, discussed based on research articles and book references, including taste, price, a comfortable place, and peer influence. Fast food can increase the risk of several diseases, such as obesity, diabetes, hypertension, and blood lipid disorders or dyslipidemia. Obesity or overweight is experienced by children, adolescents, and adults. However, from obesity experienced by a person, it will increase a person's risk factors for suffering from other degenerative diseases, such as high blood pressure, diabetes, cancer, heart disease, and stroke.